A decade of engineering computer engineers - Jovanov, Mile; Ackovska, Nevena; Stankov, Emil; Mihova, Marija; Gushev, Marjan (IEEE, 2017)
Creating an optimal conditions for producing generations of successful Computer scientists and engineers is very demanding. Many aspects have to be taken into consideration. One of the factors is the quality of the Bachelor’s education system that actually enables the diplomas in Computer Science and Engineering. However, the students enrolling in the Bachelor’s system have to be optimally prepared to follow the curriculum. In this paper we present some of the many factors that influenced the generations of Computer scientists and engineers that have earned their BSc degree in the Faculty of Computer Science and Engineering, and the institutions that preceded this Faculty in the years before 2011. Such factors, investigated in this paper are: the changes in the primary and secondary educational system and the aspects of these systems that influence the informatics knowledge of the pupils on one hand, and on the other hand the evolution of the system of competitions in informatics that sparkles the interest in the talented pupils and enables the most talented and hardworking ones to compete in the international Olympiads in informatics. As a result of improving these two parallel systems, the number of enrolled students in the faculties that teach Computer Science and Engineering has raised. Moreover, some of these pupils have turned into great entrepreneurs and have started their own successful software companies.